2010
DOI: 10.4306/pi.2010.7.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cerebral Cortex and Limbic Brain Functions after Short-Term Paroxetine Treatment in Panic Disorder: An [18F]FDG-PET Pilot Study

Abstract: ObjectivePanic disorder (PD) is a common and often chronic psychiatric illness, and serotonin-specific reuptake inhibitors (SSRIs) are the drugs of choice for the treatment of PD. Previous studies suggested the cerebral cortex and limbic brain structures played a major role in the development of PD, but the therapeutic effect of SSRIs on specific brain structures remains unclear in PD. We examined the changes in PD patients' glucose metabolism using the [18F] Fluorodeoxy-glucose-positron emission tomography (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Hodzic et al 35 suggested that the right superior and inferior parietal cortices were involved in the analysis of body-related information. 36 In the current study, in the TKD group, the cerebellum was functionally connected to the right frontal cortex, while in the control group, the cerebellum was functionally connected to the left frontal and parietal cortices. The right hemisphere is known to be associated with the sense of space and body perception.…”
Section: Discussionmentioning
confidence: 49%
“…Hodzic et al 35 suggested that the right superior and inferior parietal cortices were involved in the analysis of body-related information. 36 In the current study, in the TKD group, the cerebellum was functionally connected to the right frontal cortex, while in the control group, the cerebellum was functionally connected to the left frontal and parietal cortices. The right hemisphere is known to be associated with the sense of space and body perception.…”
Section: Discussionmentioning
confidence: 49%
“…Also, consistent with the notion that this region plays a compensatory function in the central fear circuit are findings of treatment-associated increases in activation of the VLPFC in both adults and youth. For example, treatment with the SSRI paroxetine is associated with increases in metabolic activity in this region in adults with anxiety disorders (Sim et al, 2010) and CBT in adults with anxiety disorders results in increased connectivity between the inferior frontal gyrus and the amygdala as well as the anterior cingulate cortex (Kircher et al, 2013). Additionally, one small study of adolescents with GAD revealed that successful treatment with either the SSRI fluoxetine or CBT was associated with increases in functional activation within the VLPFC (Maslowsky et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in adolescents with GAD, increased gray matter volumes were observed in precentral gyrus. To date, multiple studies have noted increased functional activity in precentral gyrus using positron emission tomography (PET) in adults with GAD, adults with generalized social phobia, and in adults with panic disorder . Importantly, this region is not only involved in motor and somatosensory functions, but is also involved in processes which may be central to anxiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple studies have noted increased functional activity in precentral gyrus using positron emission tomography (PET) in adults with GAD, [58] adults with generalized social phobia, [59] and in adults with panic disorder. [60] Importantly, this region is not only involved in motor and somatosensory functions, but is also involved in processes which may be central to anxiogenesis. For example, the precentral gyrus has been associated with the modulation of anticipatory threat [61] and has been linked with anxious attachment styles.…”
Section: Discussionmentioning
confidence: 99%